Turning The Corner: A Study of Demand Patterns and Adoption Trends of Electric Vehicles in India - B M, Lingaraja; R, Dr. Sunitha (INTERNATIONAL JOURNAL OF SCIENTIFIC RESEARCH IN ENGINEERING AND MANAGEMENT, 2025)
“The adoption of electric vehicles can make human life better” Abstract India stands at a critical juncture in its transition toward sustainable transportation, driven by growing environmental concerns, policy reforms, and advancements in electric vehicle (EV) technology. This primary research presents original, first-hand insights into the real-world factors shaping EV adoption across diverse demographics and regions within the country. Using a descriptive research design and data collected from 100 respondents through structured questionnaires, the study examines the influence of age, income, and infrastructure availability on consumer preferences toward EVs. Chi-square analysis reveals no statistically significant relationship between demographic factors such as age and income with EV ownership, indicating that these variables are not key determinants in current adoption patterns. In contrast, the availability of fast-charging infrastructure emerged as a significant factor influencing consumers’ likelihood of purchasing an EV. Respondents with greater access to charging stations were notably more open to considering EV adoption, underlining the critical role of infrastructural readiness in driving market growth. The study concludes that improving public charging facilities, launching inclusive awareness campaigns, and introducing localized policy incentives are essential strategies to accelerate EV uptake in India. By bridging the gap between policy intentions and grassroots-level consumer behaviour, this research offers a uniquely Indian perspective that is often missing in global EV discourse. The findings provide valuable, zero-plagiarism insights for policymakers, investors, and manufacturers seeking to align their strategies with the evolving realities of India's electric mobility ecosystem. Keywords: Electric Vehicles, Consumer Demands, Market Trends, EV Adoption, Brighten India, EV in Sustainability